The Relationship between Job Stress and Cyberloafing Behavior in Administrative and HR Employees of Sunan Rubber Palembang Ltd - Dwi Hurriyati; Intan Marlinda (Global Writing Academica Researching & Publishing, 2023)
This study aims to determine the relationship between work stress and cyberloafing behavior in administrative and HR employees of Sunan Rubber Palembang Ltd. The independent variable in this study is Cyberloafing Behavior, and the dependent variable is Job Stress. The population in this study are employees of Sunan Rubber Palembang Ltd, totaling 230 people. Based on the Isaac and Michael formula with an error rate of 5%, a population of 139 people is obtained. This research uses quantitative methods. The sampling technique used in this study is Simple Random Sampling. The measurement tools used in this study are the cyberloafing behavior scale and the work stress scale. The cyberloafing behavior scale has 60 items with a reliability of 0.927 and a work stress scale of 60 items with a reliability of 0.942. The data analysis technique used a simple linear regression analysis technique (single linear regression) with the SPPS version 20.0 program. based on the results of data analysis using the SPSS Version 20.0 program, the results obtained were correlation coefficient values ​​r = 0.805, R2 values ​​= 0.648, and p values ​​< α (0.05) so the results obtained were that there was a very significant relationship between work stress and cyberloafing behavior in PT employees Sunan Ruber. Work stress affects cyberloafing behavior by 64.8%, while the other 35.2% is influenced by other factors not involved in this study.